COMPETITIVE ADVANTAGE TOWARDS CREATIVE ECONOMY IN ISLAM - femei Purnamasari (Journal of Islamic Business and Economic Review, 2020)
Creative Economy is an economic concept in the new economic era that intensifies information and creativity by relying on ideas and stock of knowledge as the main production factors in its economic activities, this will certainly have an impact on performance generated in a job, which will ultimately be able to increase excellence employees at work. One of the competition in an industry is through the development of creative economy, which seeks to increase human resources in order to have the creativity, skills and talents of individuals who are economically valuable, which can be seen from competitive advantages known through the concept of work ethics in Islam or more leads to the ethos of competition in the quality of work seen from: Ash-Shalah (Good and Beneficial), Al-Itqan (Stability and Perfectness), Al-Ihsan (Doing the Best / Better), Al-Mujahadah (Hard and Optimal Work), Tanafus and Ta'awun (Competing and Helping), Observing the Value of Time. The method used in this study is descriptive qualitative, utilizing primary data sources and secondary data, using populations that are more directed to the "social situation" of the population and samples taken using probability sampling from several companies and gareli-based sharia, which are recorded in the department Lampung Province industry and Kopras service, data collection using observation, interview and documentation methods. Data management by means of data checking (editing), data marking (coding), data reconstruction (reconstructing) and data sitematization (systematizing) which are then analyzed by description and analysis. This study looks at and examines how competitive advantage can enhance the creative economy carried out by several sharia companies in Lampung Province in terms of Islamic economics. Keywords: Competitive Advantage, Creative Economy